ANALYSIS OF ELEMENTARY STUDENTS' LEARNING OBSTACLES IN UNDERSTANDING FRACTIONS: A CASE STUDY IN SOUTH CENTRAL TIMOR REGENCY - Rince Sefriana Margarita Benu; Andrian Runtius Lalang (Program Studi PGSD Universitas Flores, 2026)
Fraction material presents considerable difficulty for students due to the presence of learning obstacles. The purpose of this study is to describe the profile of learning obstacles experienced by elementary school students in understanding fractions in South Central Timor (TTS) Regency, as well as the dominant factors contributing to these obstacles. A qualitative case study design was employed. The participants consisted of 200 sixth-grade elementary school students and 10 elementary school teachers from South Central Timor Regency, East Nusa Tenggara Province. Data were collected using triangulation, combining diagnostic tests and semi-structured interviews. Data analysis followed the Miles and Huberman framework, comprising three stages: data reduction, data display, and conclusion drawing/verification. The findings revealed three types of learning obstacles: epistemological, ontogenic, and didactic. Epistemological obstacles include difficulties with modeling fractions, equalizing denominators, and applying the